(untitled) (Bangladesh Journal of Botany, 2022)
The study was conducted to utilize functional attributes of Momordica charantia juice extract by mixing with papaya pulp for imparting yellow-orangecolour of its carotenoids and aonla juice with high Vitamin C to develop Momordica charantia blended functional nectar beverage without any preservative and synthetic food colorant. The ratio of 50 : 25 : 25 of bitter gourd juice extract, aonla juice and papaya pulp with best sensory scores on a nine-point hedonic scale was optimized for the processing of the blended beverage. Functional profile in terms of quality attributes such as reducing sugars (8.39%), DPPH activity (64.20%), total phenolics (41 mg/100 ml), carotenoids (0.58 mg/100 ml), and ascorbic acid (28.8 mg/100 ml) were recorded best in organic honey-based spiced blended nectar. However, charantin content (0.111 mg/100 ml) was found highest in plain bitter gourd beverage. Organoleptic scores and rich functional profile recorded during studies strongly indicated a positive perception of consumers and the need for commercialization. Bangladesh J. Bot. 51(3): 445-453, 2022 (September)